Mitochondrial quality control and its emerging role in the pathogenesis of diabetic kidney disease - Jihyun Baek; Yu Ho Lee; Hye Yun Jeong; So-Young Lee (The Korean Society of Nephrology, 2023)
Most eukaryotic cells have mitochondrial networks that can change in shape, distribution, and size depending on cellular metabolic demands and environments. Mitochondrial quality control is critical for various mitochondrial functions including energy production, redox homeostasis, intracellular calcium handling, cell differentiation, proliferation, and cell death. Quality control mechanisms within mitochondria consist of antioxidant defenses, protein quality control, DNA damage repair systems, mitochondrial fusion and fission, mitophagy, and mitochondrial biogenesis. Defects in mitochondrial quality control and disruption of mitochondrial homeostasis are common characteristics of various kidney cell types under hyperglycemic conditions. Such defects contribute to diabetes-induced pathologies in renal tubular cells, podocytes, endothelial cells, and immune cells. In this review, we focus on the roles of mitochondrial quality control in diabetic kidney disease pathogenesis and discuss current research evidence and future directions.